Evaluating Body-Centered Interactions in an Image Search Task - Gonzalez-Ibanez, R; Varela-Otarola, J; Barrera-Pulgar, C (Association for Computing Machinery, Inc, 2016)
Interacting with information in digital environments involves a physical gap between people and information. Although current advances in interaction technology provide the means for helping bridge this gap, little is known about whether this gap affects user experience and performance in the context of information-related tasks such as information search. In this paper we present preliminary results from a larger study focused on immersive interaction with digital information objects. In particular, we report those derived from a user study designed to evaluate interactions with digital information objects through body gestures in the context of an image search task. Our results suggest that compared to traditional interactions through mouse, this type of interaction not only helps lessen cognitive workload, but also leads to achieve similar precision in terms of the information collected. © 2016 ACM.